2020
DOI: 10.5435/jaaos-d-18-00475
|View full text |Cite
|
Sign up to set email alerts
|

Intrasite Antibiotic Powder for the Prevention of Surgical Site Infection in Extremity Surgery: A Systematic Review

Abstract: Introduction: Although the role of intrasite antibiotic powder in preventing surgical site infections (SSIs) has been extensively explored in spinal surgery, it remains underevaluated in the other orthopaedic subspecialties. This systematic review examines the utilization of intrawound antibiotic powder as a prophylactic measure against SSIs in orthopaedic procedures. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The use of topical antibiotics has grown among trauma surgeons because of the potential for high local concentrations without systemic complications, along with less reliance on local blood supply that may be damaged in extremity trauma. Multiple previous studies have suggested that systemic absorption of topical antibiotics is minimal 10,12,14 . Ghobrial et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The use of topical antibiotics has grown among trauma surgeons because of the potential for high local concentrations without systemic complications, along with less reliance on local blood supply that may be damaged in extremity trauma. Multiple previous studies have suggested that systemic absorption of topical antibiotics is minimal 10,12,14 . Ghobrial et al .…”
Section: Discussionmentioning
confidence: 97%
“…The use of topical antibiotics has grown among trauma surgeons because of the potential for high local concentrations without systemic complications, along with less reliance on local blood supply that may be damaged in extremity trauma. Multiple previous studies have suggested that systemic absorption of topical antibiotics is minimal 10,12,14 . Ghobrial et al examined the adverse events associated with intrawound vancomycin in lumbar spinal surgery in 6,701 patients and found only a single case of systemic absorption, resulting in supratherapeutic vancomycin exposure 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic reviews have examined the effect of intrawound antibiotics in either instrumented spinal procedures or open limb fractures [9,[12][13][14][15][16]. Because both fields share a high risk of infection and the objective of achieving bony union, which may be affected by local antibiotics, we believe there is value in reporting pooled outcomes of local antibiotics comprehensively from both specialties.…”
Section: Introductionmentioning
confidence: 99%